Pain in Finnish female municipal employees with special reference to psychosocial and work-related factors and quality of life - Malmberg-Ceder, Kirsi (fi=Turun yliopisto|en=University of Turku|, 2022)
Pain is a major clinical, social and economic problem worldwide. Chronic pain disorders have a substantial impact on person´s life and they are a common reason for impaired work ability and disability. Musculoskeletal pain and headache are the most prevalent pain conditions and are more frequent in female population. The aim of the present study was to evaluate the relationships between common pain symptoms, musculoskeletal pain or headache, and psychosocial factors, work ability and quality of life in working-age occupational female population. The present study is part of the PORTAAT (PORi To Aid Against Threats) study, which comprises municipal employees of the city of Pori, Finland. This study consisted of female participants (n=732), the number of subjects included varied slightly in the four studies, depending on the availability of the data collected. The data was collected using validated questionnaires, which were filled in by the study subjects, and included Örebro Musculoskeletal Pain Screening Questionnaire (ÖMPSQ) (the burden of musculoskeletal pain), Headache Impact Test 6 (HIT-6) (the burden of headache), and questionnaires about psychosocial risk factors, work ability and quality of life. Among women with musculoskeletal pain psychosocial factors significantly correlate with work engagement, while the pain itself does not. Because work engagement associates positively with work ability, occupational health care should pay special attention on the psychosocial aspects in female employees with musculoskeletal pain to improve their work wellbeing and maintain their work ability. This study also confirmed that the HIT-6 questionnaire has good construct validity and it describes reliably and independently the impact of headache without interference of psychosocial factors in this kind of population. Recurrent headache and the burden of headache, measured by HIT-6, were clearly associated with presenteeism, but not with absenteeism. Recurrent headache has a significant negative impact on both healthrelated and general quality of life, also in this study population, in which anxiety and depressive symptoms scores were low. This study shows that musculoskeletal pain and headache are common among Finnish municipal female employees. Concerning musculoskeletal pain the psychosocial risk factors are more relevant in association with work well-being than the pain itself. Recurrent headache is correlated with substantial presenteeism and lowers quality of life broadly.

Kunta-alalla työskentelevien naisten kipu – mielenkiinnon kohteina psykososiaaliset riskitekijät, työhyvinvointi ja elämänlaatu Kipu on huomattava kliininen, sosiaalinen ja taloudellinen haaste maailmanlaajuisesti. Kroonisen kivun vaikutus yksilön elämään on merkittävä sekä heikentyneen toiminta- ja työkyvyn yleinen syy. Tuki- ja liikuntaelinperäinen kipu ja päänsärky ovat yleisimmät kipuoireet erityisesti naisilla. Tutkimuksen tavoitteena oli selvittää tavanomaisten kipuoireiden, tuki- ja liikuntaelinperäisen kivun ja päänsäryn sekä psykososiaalisten riskitekijöiden, työkyvyn ja elämälaadun välisiä suhteita työikäisillä naisilla. Tutkimus on osa PORTAAT tutkimusta, johon osallistui Porin kaupungin työntekijöitä. Tämä alatutkimukseen kohdistettiin naisiin (n= 732), osallistujien määrä vaihteli eri osatutkimuksissa riippuen käytettävissä olevien tietojen saatavuudesta. Osallistujat täyttivät validoidut kyselylomakkeet, mm koskien tuki- ja liikuntaelinperäisen kivun (Örebro Musculoskeletal Pain Screening Questionnaire (ÖMPSQ)) ja päänsäryn (Headache Impact Test 6 (HIT-6)) aiheuttamaa haittaa, psykososiaalisia riskitekijöitä, työkykyä ja elämänlaatua. Tuki- ja liikuntaelinperäistä kipua kokevilla naisilla psykososiaaliset tekijät korreloivat koettuun työn imuun, mutta itse kipuoireet eivät. Koska työn imu korreloi positiivisesti työkykyyn, on työterveyshuollossa syytä kiinnittää erityistä huomiota tuki- ja liikuntaelinperäistä kipua kärsivien naisten kohdalla psykososiaalisiin tekijöihin työhyvinvoinnin ja työkyvyn parantamiseksi. Tutkimuksemme vahvisti, että HIT-6 päänsärkykysely kuvaa luotettavasti päänsäryn aiheuttamaa haittaa eivätkä psykososiaaliset tekijät vaikuta tulokseen tämänkaltaisessa aineistossa. Toistuva päänsärky ja sen aiheuttama, HIT-6 kyselyn kuvaama taakka assosioitui presenteismiin (heikentynyt työkyky, mutta työntekijä on työssä), muttei absenteismiin (työstä poissaolo). Toistuva päänsärky heikensi selvästi sekä terveyteen liittyvää että yleistä elämänlaatua, myös tämänkaltaisessa populaatiossa, jossa ahdistuneisuutta ja depressiivisiä oireita oli vähän. Tutkimuksessa todettiin, että tuki- ja liikuntaelinperäinen kipu ja päänsärky ovat erittäin yleisiä suomalaisilla kunta-alalla työskentelevillä naisilla. Tuki- ja liikuntaelinperäistä kipua kokevilla psykososiaaliset riskitekijät olivat merkityksellisempiä työhyvinvoinnin kannalta kuin kipu sinänsä. Toistuva päänsärky (esim. migreeni, lihasjännityspäänsärky) heikentää selkeästi työkykyä, lisää erityisesti sairaana työskentelyä sekä huonontaa merkittävästi elämänlaatua.